Teaching Speaking Through Total Immersion Program at The Ninth Grade of SMP Negeri 3 Panca Rijang - Andi Sadapotto; Ibrahim Manda; Sam Hermansyah; Asman M (Edumaspul: Jurnal Pendidikan, 2021)
The aims of this article is to describe that total immersion program in teaching English can improve students speaking ability. This article is made from research result which used pre- test and post-test design. The population of the article is the ninth grade of SMP Negeri 3 Panca Rijang there are two classes. The writer applied random technique that took one of the two class and sample of this article was IX.2 class with 20 students. The instrument of this article was speaking test which would be administred in pre-test and post-test. The pre-test would be used to find the prior knowledge of speaking ability, while post-test would be used to find speaking ability achievement after treatment is given. The result of this article showed that total immersion program was effective to improve speaking ability at the ninth grade of SMP Negeri 3 Panca Rijang especially IX.2 class. It could be proved from their mean score in post-test (56.95) was higher than their mean score in pre-test (48.50), and the t-test value (10.934) was greater than t-table (a = 0.05; df= 9; t table = 2.262, this means that H1 was accepted.